Características poblaciones de Rattus rattus y Mus musculus presentes en comunidades rurales de Yucatán, México - Panti May, Jesús Alonso; Gurubel González, Yessica M.; Palomo Arjona, Eduardo E.; Cetina Trejo, Rosy C.; Machain Williams, Carlos; Robles, Maria del Rosario; Hernández Betancourt, Silvia F.
The aim of this study was to describe the abundance, weight and body length structures, and reproductive and health status of the black rat Rattus rattus and the house mouse Mus musculus from Yucatán, México. Rodents were trapped from May to September 2016 in rural households in the communities Xkalakdzonot (XKA) and Paraíso (PAR). A total of 236 M. musculus and 127 R. rattus were trapped over 3880 trap-nights. In XKA, R. rattus was more abundant than M. musculus, whereas in PAR, M. musculus was notably dominant over R. rattus. The sex ratio was 1:1 in both rodent species. Rattus rattus in classes 40.1?80 g and 120?139 mm were more abundant, whereas M. musculus in classes 8.1?12 g and 70?79 mm were more abundant. Mus musculus had similar weight, body length and reproductive and health parameters between communities. The majority of specimens of trapped rodents had a good body condition and few individuals had wounds. The information generated in this study is basic for understanding the ecology of commensal rodents, the dynamics of rodent-associated zoonosis transmission, and to design of integrated control programs for rodents. Fil: Panti May, Jesús Alonso. Universidad Autonoma de Yucatan; México Fil: Gurubel González, Yessica M. Universidad Autonoma de Yucatan; México Fil: Palomo Arjona, Eduardo E. Universidad Autonoma de Yucatan; México Fil: Cetina Trejo, Rosy C. Universidad Autonoma de Yucatan; México Fil: Machain Williams, Carlos. Universidad Autonoma de Yucatan; México Fil: Robles, Maria del Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Hernández Betancourt, Silvia F. Universidad Autonoma de Yucatan; México